Missionary activity of the orthodox monasteries of Transbaikal within the framework of the existence of the second Transbaikal ecclesiastical mission - Drobotushenko, Evgeny V.; Lantsova, Yulia N.; Kamneva, Galina P.; Sotnikov, Andrey A.; Sotnikov, Sergey A. (Linguistics and Culture Review, 2021)
The Second Transbaikal Ecclesiastical Mission significantly changed the situation with the spread of Orthodoxy among the indigenous population of the region – the Buryats, who, for the most part, were adherents of the northern branch of Buddhism – Lamaism. Its activities also had a significant impact on the Old Believer population of the region. The paper analyses the features of the activities of the Orthodox monasteries of Transbaikal, carried out by them within the framework of the missionary work of the second Transbaikal Ecclesiastical Mission, which in many ways changed the situation with Orthodoxy in the region. The mission began its work in 1861 (according to other sources, in 1862) and focused its activities on spreading Orthodoxy among the local Buryat population, predominantly Lamaists, and Old Believers. The author notes that this subject matter is understudied. At the same time, references are made to some archival documents. The result of the study was the conclusion that the Orthodox monasteries of the region quite actively took part in missionary activities.